PROPERTIES OF EPOXY COMPOSITES, IMPREGNATED BY PHYTIC ACID - Chernyavska, Tatiana (Scientific Journal "Metallurgy", 2021)
Epoxy diane oligomer ED-20, polyethylene polyamine PEPA hardener and microdispersed particlesof phytic acid were used to form composite materials and protective coatings for thetransport industry. It is important to improve the properties of materials designed to increase thereliability and repair of vehicles, is the use of chemically active to the interfacial interaction ofdispersed fillers. In this regard, it is interesting to use as a modifying additive dispersed particlesof phytic acid. Phytic acid is an organic environmentally friendly product, active in physicochemicalinteraction with organic and synthetic substances, which will improve the mechanicaland thermophysical properties of protective coatings. It was believed that due to the activity ofthe surface of the particles and their slight dispersion (d = 8… 10 μm) it is advisable to introduceinto the epoxy oligomer additive at homeopathic content (in the amount of 0.25…1.00 parts byweight per 100 parts by weight of epoxy oligomer ED-20). The dependence of themicrodispersed powder content on the adhesive, physical and mechanical properties and heatresistance of epoxy composites has been studied. It is proved that for the formation of a compositematerial or protective coating with improved adhesion and cohesion properties, the optimalcontent of particles is 0.25 wt. h. per 100 parts by weight epoxy oligomer ED-20. Such materialsare characterized by increased mechanical strength and the ability to withstand static andshock loads, as their properties are significantly increased compared to the properties of thematrix material. The results of experimental studies of the physical and mechanical properties ofcomposite materials are in good agreement with the results of tests of samples with adhesivecharacteristics, which indicates their reliability.